MENINGKATKAN KESADARAN LINGKUNGAN WIRAUSAHAWAN MUDA MELALUI WORKSHOP EKONOMI HIJAU - Salsabila Azzahra (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
In an era of rapid development and change, awareness of the importance of the environment is becoming increasingly urgent. Green economy is a concept that emphasizes sustainable and environmentally friendly economic development. The application of green economic principles can produce economic growth that is consistent with efforts to protect the environment and utilize natural resources wisely. With the implementation of this community service to provide awareness to SMKN 1 Cikande students that the importance of implementing a green economy to protect the environment and the business opportunities that we can get by implementing a green economy. With this, we the PKM team want to carry out socialization to introduce the concept of green economy, objectives, impacts if the lack of application of green economy, application techniques, and how to take advantage of business opportunities in the green economy era. The method used is conceptual and participatory, where participants are invited to actively contribute to the activities, including in delivering materials, fun games, and discussions. The community service activity was realized on May 17, 2024 at SMKN 1 Cikande and was attended by 27 students from class XI of the accounting department of SMKN I Cikande. Education through green economy workshops can be an effective way to increase environmental awareness among young entrepreneurs. with the implementation of this activity, the community can increase their awareness of protecting the surrounding environment. Keywords: Green Economy; Business Opportunities; Environment